Bubble mapping with the Square Kilometre Array – I. Detecting galaxies with Euclid, JWST, WFIRST, and ELT within ionized bubbles in the intergalactic medium at z > 6. Issue 1 (17th January 2020) - Zackrisson, Erik; Majumdar, Suman; Mondal, Rajesh; Binggeli, Christian; Sahlén, Martin; Choudhury, Tirthankar Roy; Ciardi, Benedetta; Datta, Abhirup; Datta, Kanan K; Dayal, Pratika; Ferrara, Andrea; Giri, Sambit K; et al.
ABSTRACT: The Square Kilometre Array (SKA) is expected to provide the first tomographic observations of the neutral intergalactic medium at redshifts z > 6 and pinpoint the locations of individual ionized bubbles during early stages of cosmic reionization. In scenarios where star-forming galaxies provide most of the ionizing photons required for cosmic reionization, one expects the first ionized bubbles to be centred on overdensities of such galaxies. Here, we model the properties of galaxy populations within isolated, ionized bubbles that SKA-1 should be able to resolve at z ≈ 7–10, and explore the prospects for galaxy counts within such structures with various upcoming near-infrared telescopes. We find that, for the bubbles that are within reach of SKA-1 tomography, the bubble volume is closely tied to the number of ionizing photons that have escaped from the galaxies within. In the case of galaxy-dominated reionization, galaxies are expected to turn up above the spectroscopic detection threshold of JWST and ELT in even the smallest resolvable bubbles at z ≤ 10. The prospects of detecting galaxies within these structures in purely photometric surveys with Euclid, WFIRST, JWST, or ELT are also discussed. While spectroscopy is preferable towards the end of reionization to provide a robust sample of bubble members, multiband imaging may be a competitive option for bubbles at z ≈ 10, due to the very small number of line-of-sight interlopers expected at these redshifts.